The Cost of Acute Respiratory Infections With Cough Among Urban Aboriginal and Torres Strait Islander Children - Lovie-Toon, Yolanda G.; McPhail, Steven M.; Au-Yeung, Yin To; Hall, Kerry K.; Chang, Anne B.; Vagenas, Dimitrios; Otim, Michael E.; O'Grady, Kerry-Ann F. (Frontiers in Pediatrics, 2018)
Introduction: Acute respiratory infections with cough (ARIwC) contribute considerably to childhood morbidity, yet few studies have examined the cost of these illnesses among Australian children. Moreover, of the few studies that have, none are inclusive of Aboriginal and/or Torres Strait Islander children, despite this population experiencing a greater burden of respiratory illnesses. This study aimed to determine the costs of ARIwC among urban Aboriginal and/or Torres Strait Islander children from the perspective of caretakers, the public healthcare system and employers. Methods: This cost of illness study used data collected from Aboriginal and/or Torres Strait Islander children aged <5 years enrolled in a 12 month prospective cohort study conducted through an urban primary healthcare clinic in Queensland, Australia. Illness-related resource use was collected for each episode of ARIwC reported, and costed at market rates. Linear regression was used to a) examine cost per episode by season of illness onset and cough duration and b) examine cost per month of observation by baseline child and family characteristics. Results: During the study period, a total of 264 episodes of ARIwC were reported among 138 children. The total mean cost was estimated to be $AU252 per non-hospitalized episode (95%CI 169-334). Caretakers, the public healthcare system and employers incurred 44%, 39% and 17% of costs per episode, respectively. After accounting for months of completed follow-ups, the total mean cost per child per year was estimated to be $991 (95%CI 514-1468). Winter episodes and episodes resulting in chronic cough were associated with significantly higher costs per episode. A prior history of wheezing, connections to traditional lands and parent/guardian belief that antibiotics should be given until symptoms resolved were associated with significantly higher cost per child month of observation. Conclusion: The cost of ARIwC in this predominantly disadvantaged population is substantial, particularly for caretakers and this needs to be considered in both clinical management and public health initiatives. The importance of cultural factors on health and burden of illness should not be overlooked. Further research into the prevention of chronic cough may play an important role in reducing the economic burden of pediatric respiratory infections.